The fertilization problems of cultivated red- and black currant varieties in Hungary - Porpáczy, A. (International Journal of Horticultural Science, 2002)
Small fruits have a modest share in the fruit production of Hungarys. Red currant was grown traditionally in home gardens 60-70 years ago. Commercial production was established only in the surroundings of some town. The black currant was unknown until after Wold War II. An important change occured in small fruit production in the 1950s. Socialist countries, which had cheaper labour power, made efforts to meet these demands. In this time we produced 25.000 t.Presently the country produces 13-15.000 tons currant fruit yearly 60% from this is black currant, which has a better market. It is our own interest to make our currant production more profitable. The currant is the second most widely cultivated soft fruit. Our product is disposed mostly on EU markets.There was no breeding activity in this field in Hungary earlier. Cultivars used were mostly of foreign origin (W. European; Boskoop Giant, Silvergieter, Wellington XXX, Russian; Altaiskaya Desertnaya, Neosupaiuschaiasya, N. European; Brikltorp, Ojebyn). Besides well-known advantageous this cultivars have also some defects mainly unfavourable—adaptation to climatic conditions, which caused fertilisation problems, reduced the fruit set and uneven growth with decreased yields (Dénes & Porpáczy, 1999). About 140 black currant cultivars were investigated during the last four decades in our variety trials and only four of them were introduced with satisfying yielding capacity (3.5-5.5 t/ha).